1978
DOI: 10.1002/path.1711250303
|View full text |Cite
|
Sign up to set email alerts
|

The pathology of experimental Ebola virus infection in monkeys

Abstract: Six rhesus and two vervet monkeys were infected intraperitoneally with Ebola virus. They developed an acute haemorrhagic fever with skin rash 4 days later and died 6--12 days after infection. Histopathological lesions of acute necrosis were present in the liver, spleen, lymph nodes, lungs and testes. The presence of fibrin thrombi in several organs was suggestive of the occurrence of disseminated intravascular coagulation during the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 10 publications
7
78
0
Order By: Relevance
“…Results from many studies have shown biochemical and histological evidence of disseminated intravascular coagulation in both experimentally infected NHPs and humans 19,20,22,23,40,[44][45][46][49][50][51]53,54,70,[73][74][75][76][77][78][79] . The mechanisms that cause these coagulation disorders are not fully understood, but the expression or release of tissue factor from filovirus-infected monocytes and macro phages seems to play a role 54,55 .…”
Section: Type I Transmembrane Proteinmentioning
confidence: 99%
“…Results from many studies have shown biochemical and histological evidence of disseminated intravascular coagulation in both experimentally infected NHPs and humans 19,20,22,23,40,[44][45][46][49][50][51]53,54,70,[73][74][75][76][77][78][79] . The mechanisms that cause these coagulation disorders are not fully understood, but the expression or release of tissue factor from filovirus-infected monocytes and macro phages seems to play a role 54,55 .…”
Section: Type I Transmembrane Proteinmentioning
confidence: 99%
“…The coagulation picture is clearer for nonhuman primates. Numerous studies showed histological and biochemical evidence of DIC syndromes in EBOV infection of a variety of nonhuman primate species [32,33,[38][39][40][41][42][43][44][45][46][47].…”
Section: Animal Models Of Ebola Hfmentioning
confidence: 99%
“…EBOV replicates to high titers in the liver (12)(13)(14), and fatal infection is associated with alterations in circulating enzyme levels indicative of liver damage (15)(16)(17). Microscopic analysis of infected livers shows histopathologic lesions, including hepatocyte damage and death (14,18,19). However, previous studies have not described apoptosis as a mechanism of cell death in hepatocytes during EBOV infection.…”
mentioning
confidence: 99%